Ambient temperature effects on user thermal sensation with a simulated tablet computer. (September 2015) - Zhang, Han; Hedge, Alan; Guo, Beiyuan
A tablet computer's surface temperature can reach levels that can lead to user discomfort, especially in a warm environment. The ambient environments in which tablet computers are used can also vary. To understand how users perceive the heat from tablet computers, a laboratory study was conducted with controlled surface temperatures and ambient temperatures. A positive relationship between surface temperature and participants' thermal sensation scores was found. Participants' thermal responses to the surface heat of a simulated tablet were also moderated by the indoor temperature. Higher surface temperature (44°C) was rated less warm in cool environment than hot environment, while lower surface temperatures (34-38°C) were rated warmer in cool than hot environment. The thermal responses corresponding to the tablet surface temperatures and ambient temperatures will be helpful for setting future tablet computer heat dissipation design limits.